PERAN DAN MANFAAT KELEMBAGAAN KELOMPOK TANI PELESTARI HUTAN DALAM PENGELOLAAN TAMAN HUTAN RAYA NIPA-NIPA - Anas Nikoyan; Safril Kasim; Zakiah Uslinawaty; Rita Yani (PERENNIAL, 2020)
Kelompok Tani Pelestari Hutan (KTPH) is a community organization of farmers around the forest. KTPH was formed to provide benefits to the community and forests to remain sustainable. This study aims to determine the role and institutional benefits of KTPH in the management of Nipa-Nipa Forest Park (TAHURA). This study used a survey/interview method for all members of the Tahura Nipa-Nipa forest conservation group and analyzed descriptively. The results of the study provide an overview of the institutional benefits of farmer groups for members. These benefits are that members can exchange farming experience, can exchange work skills in managing the Tahura Nipa-Nipa area. At the same time, the institutional role of farmer groups in the management of Nipa-Nipa Forest Park is capable of handling Tahura with the principle of agroforestry. Overall the forest conservation group (KTPH) in Tahura Nipa Nipa has benefits and roles in improving the economics of the members and, at the same time, maintaining the function of the Tahura to remain sustainable.